Acute Exacerbations of Chronic Obstructive Pulmonary Disease (AECOPD) as a Cardiovascular Risk Factor - Buklioska Ilievska, Daniela; Minov, Jordan (Publi Créations, 2020)
Background: AECOPD are accompanied by increased cardiovascular risk because of systemic inflammation, hypoxia, age, cigarette smoking. Recent data suggest an increased risk of myocardial infarction in the following days of a severe exacerbation of COPD, and around 30% die from cardiovascular diseases. Cardiac dysfunction in AECOPD is often underestimated and underdiagnosed at the time of admission, because decompensated cardiac failure and AECOPD share symptom similarities. Objective: To investigate the presence of increased cardiovascular risk in hospitalized patients with emphysema and AECOPD. Materials and Methods: Observational study, 120 hospitalized AECOPD patients and 60 stable COPD controls, matched by age, gender and body mass index. Inclusion criteria: age 40–75, cigarette smoking history >=10 pack/years, signed consent for participation. All patients underwent laboratory tests, pulmonary function tests, chest-X ray, electrocardiogram (ECG), 2D-Doppler echocardiography. Results: Systolic or diastolic left ventricular dysfunction was noted in 66.7% of investigated group. Right ventricular (RV) abnormalities were significantly higher in investigated group than controls (p<0.001), with RV systolic dysfunction in 62.5%, pulmonary hypertension 54,2%, tricuspid regurgitation 53.3%. According to ECG findings 67% had abnormal ECG, and 33% had a new abnormality from baseline. Atrial premature beats were detected in 66.7%, ventricular premature beats 41.7%, un-sustained ventricular tachycardia 5%, atrio-ventricular block of first degree 5%, right bundle branch block 33.3%, atrial fibrillation 15%, T-wave changes 33.3%, ECG signs of previous infarction in 25%. An abnormal ECG, particularly with ischemic changes, on presentation to the emergency department with AECOPD, is correlated with a prolonged hospital stay (Image 1). AECOPD is associated with greater prolongation of P wave dispersion than in stable COPD. Patients with fatal arrhythmias had QTc interval greater than 440ms. Elevated troponins have been associated with the elderly, comorbid heart failure, chronic renal failure, atrial fibrillation. Correlation between pH value and fatal arrhythmias risk in investigatedgroup, showed that respiratory acidosis was associated with higher risk of fatal outcome (p<0.001). Conclusions: Acute exacerbations of COPD may trigger cardiac events. Cardiac treatments could improve AECOPD outcomes induced by respiratory infections in COPD patients, so early detection of unrecognized coexisting cardiac disorders is significant. Further research into the pathogenesis and treatment of acute cardiac dysfunction in COPD exacerbations are needed.
Keywords: Chronic Obstructive Pulmonary Disease; acute exacerbations; systemic inflammation; cardiovascular risk